2
$\begingroup$

Q: If $\alpha$ and $\beta$ are different complex numbers with $ |\beta|=1$, then find $ \bigl|\cfrac{\beta - \alpha}{1- \bar \alpha \beta}\bigr|$

[correct answer is $1$]


My proof: Let $ \alpha = a+ \iota b$ and $\ \beta = c + \iota d$

Since $|\beta| = 1 \implies \beta = 1,-1$ [opening modulus]

Required: $ \cfrac{|\beta - \alpha|}{|1- \bar \alpha \beta|}$



Case 1: When $ \beta =1$
$$ \implies \cfrac{|(1) - \alpha|}{|1- \bar \alpha (1)|} $$ $$ \implies \cfrac{|(1) - (a+\iota b)|}{|1- (a-\iota b)|} = \cfrac{|(1) - a -\iota b|}{|1- a+ \iota b|} = \cfrac{|(1 - a) -(\iota b)|}{|(1- a) + (\iota b)|} $$ Since modulus of a complex number of the form $z = x+ \iota y$ is $|z| = \sqrt{x^2+y^2} $
$$\implies \require{cancel} \frac{\cancel{\sqrt{(1-a)^2+(-b)^2}}}{\cancel{\sqrt{(1-a)^2+(-b)^2}}} = 1$$



Case 2: When $\beta = -1$
$$ \implies \cfrac{|(-1) - \alpha|}{|1- \bar \alpha (-1)|} $$ $$ \implies \cfrac{|(-1) - (a+ \iota b)|}{|1 + (a - \iota b)|} = \cfrac{|(-1 - a) - (\iota b)|}{|(1 + a) - (\iota b)|} $$ [ the below part is where I think that my solution is wrong ] $$ \implies \cfrac{\sqrt{(-1)(1+a)^2+(-b)^2}}{\sqrt{(a-1)^2+(b)^2}} $$ $$ \implies \cfrac{ \sqrt{ 1+a^2-2a+b^2 } }{ \sqrt{ 1+a^2-2a+b^2 } } $$


If my solution is wrong, how can it be corrected?



EDIT:
one error I identified when opening the identities in numerator and denominator:
Numerator: $ \bigl((-1)^2 + a^2 -2(-1)(a) \bigr) +b^2 = 1+a^2+2a+b^2$
Denominator: $ \bigl( (a)^2 + (-1)^2 + 2(-1)(a) \bigr) + b^2 = 1+a^2 -2a +b^2 $

I don't understand why this way can't work.

$\endgroup$
  • 2
    $\begingroup$ Why does $|\beta| = 1$ impply that $\beta = 1$ or $-1$? There can be many choices for $\beta$, for example $i,-i$, etc. Note we are speaking of the complex modulus, not the real modulus, since $\beta$ is a complex, not necessarily real number. $\endgroup$ – астон вілла олоф мэллбэрг Aug 9 '18 at 16:38
  • 1
    $\begingroup$ $$ z=\cfrac{\beta - \alpha}{1- \bar \alpha \beta} $$ $$ z \bar z= \left (\cfrac{\beta - \alpha}{1- \bar \alpha \beta} \right ) \left (\cfrac{\bar \beta - \bar \alpha}{1- \alpha \bar \beta} \right ) =\cfrac{\beta \bar \beta-\bar \alpha \beta -\alpha \bar \beta+\alpha \bar \alpha} {1-\bar \alpha \beta -\alpha \bar \beta+\alpha \bar \alpha \beta \bar \beta} $$ $$ z \bar z =\cfrac{|\beta|^2-\bar \alpha \beta -\alpha \bar \beta+|\alpha|^2} {1-\bar \alpha \beta -\alpha \bar \beta+|\alpha|^2|\beta|^2} $$ So if $|\beta|=1$, unless $\alpha=\beta$, $|z|=1$ $\endgroup$ – NMK Aug 9 '18 at 17:06
1
$\begingroup$

So, you have a couple of things wrong here

First, $\beta \in \mathbb{C}$, so we can't simply assume $\beta \in \{1, -1\}$, what about $\beta \in \{ z \in \mathbb{C}: \lvert z\rvert=1\}$ which contains all of the complex numbers of the form $z = 1*[cos\theta+i*sin\theta]$

As far as the proof, it is quite simple. You should look up "modulus properties" and "complex number properties"

Things I used:

$\lvert z \rvert = \lvert \bar{z} \rvert$

$\lvert z \rvert \lvert w \rvert = \lvert zw \rvert$

$z*\bar{z} = \lvert z \rvert ^2$

Let me get you started.

We know $\lvert \beta \rvert = 1$, so we can also know that $\lvert \bar{\beta} \rvert = 1$ by property 1.

We use this to take:

$ \dfrac{\lvert\beta-\alpha\rvert}{\lvert1-\bar{\alpha}\beta\rvert}*1 = \dfrac{\lvert\beta-\alpha\rvert}{\lvert1-\bar{\alpha}\beta\rvert}*\lvert\bar{\beta}\rvert $

Then we use property 2 to get $\lvert \bar{\beta} \rvert$ into our numerator.

$\dfrac{\lvert\beta\bar{\beta}-\alpha\bar{\beta}\rvert}{\lvert1-\bar{\alpha}\beta\rvert}$

Finally, it is up to you to find why this is $1$

$\endgroup$
1
$\begingroup$

In $\mathbb{C}$ if $|\beta|=1$ then $\beta$ can be anywhere on the unit circle centred at $0$. In particular,

$$\vert{\beta}\vert=1 \iff \beta\in \{e^{it}:t\in[0,2\pi)\}$$

A general trick when working with $\vert z \vert$ is to use the fact that $\vert z \vert^2=z \bar{z}$. So:

$$\begin{align} \left\lvert \cfrac{\beta - \alpha}{1- \bar \alpha \beta}\right\rvert^2 &= \left(\cfrac{\beta - \alpha}{1- \bar \alpha \beta}\right) \overline{\left(\cfrac{\beta - \alpha}{1- \bar \alpha \beta}\right)} \\ &= \left(\cfrac{\beta - \alpha}{1- \bar \alpha \beta}\right) \left(\cfrac{\bar{\beta} - \bar{\alpha}}{1- \alpha \bar{\beta}}\right) \end{align}$$

By expanding this bracket and cancelling, you should find your solution!

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.